Smarter Hypnobirthing Intervention to Reduce Anxiety and Improve Maternal Birth Outcomes among Primigravid Women in Samarinda, Indonesia - Besse Lidia; Nuuva Yusuf; M. Ardan; Nur Aisyah; Jesika Marselia Tuko (Jurnal EduHealth, 2025)
Anxiety among primigravida women is a serious concern that can affect maternal mental health, prolong labor, intensify pain, and trigger obstetric complications. Non-pharmacological interventions such as Smarter Hypnobirthing offer an integrative approach that combines relaxation techniques, positive affirmations, education, and family support. This study aimed to evaluate the effectiveness of Smarter Hypnobirthing in reducing anxiety levels among primigravida pregnant and postpartum women in Samarinda, Indonesia. A quasi-experimental design with a pre-post test and control group was employed. A total of 40 participants were equally assigned to the intervention group (n=20) and the control group (n=20). The intervention group received the Smarter Hypnobirthing program, while the control group received only basic midwifery counseling. Anxiety levels were measured before and after the intervention using standardized instruments. The intervention group demonstrated a significant reduction in anxiety scores (Δ = -8.15; p < 0.001), whereas the control group showed only a minor and non-significant decrease (Δ = -1.15; p = 0.082). Posttest comparisons between groups revealed a meaningful difference (14.20 vs. 20.75; p < 0.001). Smarter Hypnobirthing effectively reduces anxiety among primigravida pregnant and postpartum women. This approach has the potential to serve as an innovative, non-pharmacological intervention that promotes maternal well-being, aligning with the global agenda of the Sustainable Development Goals (SDGs).